2020
DOI: 10.1109/access.2020.2986482
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Electrical Tree Discharge in Epoxy Resin Impregnated Paper Insulation

Abstract: An electrical tree discharge model of multilayer insulation paper was prepared, and a voltage of 20 kV was used for electrical tree cultivation and initiation tests. Based on the microscopic image information and partial discharge (PD) information during the aging of the electrical tree, the development of electrical tree discharges between layers of paper comprising epoxy resin-impregnated paper insulation was studied. The results show that, by analysing PD information such as the discharge volume phase spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The formation of free radicals in polymer would lead to a free-radical chain reaction and subsequently the generation of low-molecular products (e.g., hydroxyl, epoxy, etc.) [ 30 , 31 ]. The local area with the low-molecular products is called low-density regions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of free radicals in polymer would lead to a free-radical chain reaction and subsequently the generation of low-molecular products (e.g., hydroxyl, epoxy, etc.) [ 30 , 31 ]. The local area with the low-molecular products is called low-density regions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the development process of the electrical tree discharge went through the initial, growth, stagnation, and rapid development stages, in which the suppression of space charge in the stagnation stage reduces the rate of forward extension of the main path of the electrical tree. 23 Zhikang Yuan et al investigated the growth law of electrical trees in glass fiber/epoxy composites. It was found that when the breakdown strength of the interface was the same as that of the air gap, the electrical tree at the interface showed a "linear growth".…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wang et al investigated the development process of the electrical tree discharge between the layers of epoxy resin-impregnated paper. The results showed that the development process of the electrical tree discharge went through the initial, growth, stagnation, and rapid development stages, in which the suppression of space charge in the stagnation stage reduces the rate of forward extension of the main path of the electrical tree . Zhikang Yuan et al investigated the growth law of electrical trees in glass fiber/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, because the above study used an interface perpendicular to the electric field direction, the role of the interface in the development of electrical trees is difficult to observe. Considering that the paper is an uneven structure, a model based on E51 epoxy resin (ER)‐impregnated kraft paper was produced to simulate the edge structure, whose results showed that the interface had an induced effect on electrical tree development [14]. However, a real dry‐type bushing core mainly uses special crepe paper and ER material with ultra‐long available time at temperatures below 60°C.…”
Section: Introductionmentioning
confidence: 99%